2016
DOI: 10.1002/ieam.1820
|View full text |Cite
|
Sign up to set email alerts
|

An integrated vegetated ditch system reduces chlorpyrifos loading in agricultural runoff

Abstract: Agricultural runoff containing toxic concentrations of the organophosphate pesticide chlorpyrifos has led to impaired water body listings and total maximum daily load restrictions in California's central coast watersheds. Chlorpyrifos use is now tightly regulated by the Central Coast Regional Water Quality Control Board. This study evaluated treatments designed to reduce chlorpyrifos in agricultural runoff. Initial trials evaluated the efficacy of 3 different drainage ditch installations individually: compost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Phytoremediation, the use of living vegetation to remove or help foster degradation of contaminants from water or sediment/soil sources (UNEP, 2002), is a successful technology being integrated into various management practices. Selection of vegetation type is a key determinant in the potential success of phytoremediation efforts (Moore et al, 2001, 2007, 2008, 2017; Phillips et al, 2017). Particularly in agricultural settings, vegetation selection is critical so as not to introduce any potential noxious weeds or other plants of concern into the ecosystem.…”
mentioning
confidence: 99%
“…Phytoremediation, the use of living vegetation to remove or help foster degradation of contaminants from water or sediment/soil sources (UNEP, 2002), is a successful technology being integrated into various management practices. Selection of vegetation type is a key determinant in the potential success of phytoremediation efforts (Moore et al, 2001, 2007, 2008, 2017; Phillips et al, 2017). Particularly in agricultural settings, vegetation selection is critical so as not to introduce any potential noxious weeds or other plants of concern into the ecosystem.…”
mentioning
confidence: 99%
“…Vegetated treatment systems are usually drainage ditches that have been planted with grass or similar vegetation that can slow the flow and infiltrate runoff from agricultural fields. Research has demonstrated that VTSs, used individually or as part of a suite of management practices, reduce pesticide loads in tailwater runoff [ 3 , 4 , 5 , 6 , 7 ]. Treating irrigation water with polyacrylamide (PAM), a long-chain polymer used for erosion control, can also reduce the suspended sediments in runoff by more than 90% [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treating irrigation water with polyacrylamide (PAM), a long-chain polymer used for erosion control, can also reduce the suspended sediments in runoff by more than 90% [ 8 , 9 ]. The addition of compost and granulated activated carbon (GAC) to a grass-lined ditch has been shown to reduce the load of chlorpyrifos, an intermediately soluble pesticide, by up to 98% [ 7 ]. Integrated vegetated treatment systems have also been shown to reduce pesticide-associated toxicity to invertebrates in runoff [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations